The Influence of Employer Branding Dimensions on Generation Z Women’s Intention to Apply For a Job with Person-Organization Fit as Mediating Variable: A Study of Bandung Institute of Technology - Fadilah, Anditha Nur; Putranto, Nur Arief Rahmatsyah (Journal Integration of Social Studies and Business Development, 2023)
An organization's innovation potential is highly correlated with its ability to use its intellectual and organizational knowledge resources. Consequently, hiring high-potential individuals is one of the key issues for businesses looking to maintain a competitive advantage in the sector. However, the workforce is experiencing a demographic shift as Generation Z enters the job market in significant numbers. Given that Generation Z will ultimately dominate the workforce, this demographic shift poses a long-term challenge for businesses to understand their demands, preferences, and factors impacting their interest in applying for jobs. Additionally, establishing gender equality and increasing the involvement of women in the workforce are top recruitment goals for businesses today. In light of these circumstances, this study examines how different aspects of employer branding influence Generation Z women's intention to apply for a job and whether the person-organization fit plays a mediating role. The research employs a quantitative approach, distributing questionnaires to 335 female students of Generation Z at Bandung Institute of Technology, which will be analyzed using PLS-SEM (Partial Least Squares Structural Equation Modeling). The findings demonstrate that within the context of Generation Z at Bandung Institute of Technology, four of the five employer branding dimensions—development, economic, application, and interest value—significantly and positively impact the intention to apply for a job. However, the study also indicates that person-organization fit does not act as a mediating variable in this regard. This research offers valuable insights to companies, allowing them to improve their existing employer branding strategies and enhance their recruiting and talent acquisition approaches. By effectively attracting, engaging, and retaining Generation Z women in the workforce, companies can foster greater gender diversity and equality in the present job market.